Digital Technology of Assesment the Power Capacity of Tractor Fleet of an Agricultural Enterprise - V. V. Alt; O. F. Savchenko; O. V. Elkin (Сельскохозяйственные машины и технологии, 2019)
One of the important ways to increase the efficiency of using machinery and tractors is to ensure operating control of the power capacity of tractors employed in agricultural enterprises. It is shown that power loss of tractors and their decreased traction properties result in increased fuel consumption by 10-15 percent as well as increased operating costs. (Research purpose) To develop a digital technology of assessing the power capacity of the internal combustion engines (ICE) of the tractor fl eet employed in agricultural enterprise and develop a confi guration of software and hardware based on modern information technologies for data collection and processing. (Materials and methods) The authors used a dynamic method of ICE diagnostics using test cyclic eff ects, modeling measurements of a diagnostic signal against the background of hindrances, and an analysis of measuring information for power calculation purposes. A structural diagram of the diagnostic device performing necessary technological operations has been off ered as a result. The authors also conducted pilot studies of using digital technology for assessing the power capacity of the tractor fl eet employed in an agricultural enterprise. (Results and discussion) The authors have developed an algorithm of ICE power calculation in real time taking into account speed considerations and developed a diagnostic device providing data recording, calculation of ICE speed and power characteristics, as well as information support of the entire production cycle. It has been determined that the increased fuel consumption necessary to maintain the rated value of the tractor engine power during the observation period averaged 6525 kilograms per year, and the fuel cost, taking into account the average wholesale price of diesel fuel, reached 206,837 rubles. The authors have shown a possibility of reducing costs required to maintain the detected power deviations due to excessive fuel consumption through timely repair and adjustment-and-control actions. They have evaluated possible directions of further development of the digital technology and devices. (Conclusions) The authors have proposed a digital technology and a diagnostic device for evaluating the power of internal combustion tractor engines under production conditions. The proposed technology and diagnostics device are recommended for use by agricultural enterprises as an operating control instrument of the power supply of fi eld works to ensure the efficient operation of the tractor fl eet and provide for cost reduction.